An Initial Survey of the Performances of Exome Variant Analysis and Clinical Reporting Among Diagnostic Laboratories in China - Zhang, Kuo; Lin, Guigao; Han, Dongsheng; Han, Yanxi; Wang, Jian; Shen, Yiping; Li, Jinming (Frontiers in Genetics, 2020)
Exome sequencing has become an effective diagnostic method for Mendelian disorders. But the quality of services differed widely across laboratories in China, particularly in variant classification, even with the adoption of the ACMG guidelines. As an effort of quality control and improvement for better clinical utilization of exome sequencing, we assessed the exome data analysis and clinical reporting among Chinese laboratories. Five raw datasets of real clinical samples with associated phenotypes were sent to 53 laboratories. The participants independently performed secondary analysis, variant classification and reporting. The first round of results was used for identifying problems associated with these aspects. Subsequently, we implemented several corrective actions and a training program was designed based on the identified issues. A second round of five-case dataset was sent to the same participants. We compared the performances in variant interpretation and reporting. 85.7% (42/49) of participants correctly identified all the variants related with phenotype. Many lines of evidence of ACMG guidelines were incorrectly utilized, which resulted in a large inter-laboratory discrepancy. After training, the evidence usage problems significantly improved, leading to a more consistent outcome. Participants improved their exome data analysis and clinical reporting capability. Targeted training and a deeper understanding of ACMG guidelines helped to improve the clinical exome sequencing service in terms of consistency and accuracy in variant classification in China.